Creating a community of acceptance: increasing job opportunities and access to nature for the developmentally disabled in Mexico, Missouri - Finck, Caroline Leona (Kansas State University, 2022)
While there are over six million developmentally disabled Americans living in the country, the mental healthcare system in rural Missouri and throughout the rural United States does not adequately address the needs of the developmentally disabled. As a result, individuals lead a life mostly confined to the indoors, socially isolated, and without appropriate job opportunities—all of which the reinforce public stigmatization. In contrast, the community of Geel, Belgium has welcomed the mentally ill and developmentally disabled since the Middle Ages and has created an adult foster care system to support this population in their community. Although nothing comparable to Geel, some American communities have created similar supportive systems for developmentally disabled individuals and other vulnerable populations. In New York City, Broadway Housing Communities offers permanent supportive housing and operates as a nucleus of the community. Building Ohana in Spokane, Washington is designing an intentionally intergenerational and neurodivergent supportive community based upon community workshops from the conception of design. In Missouri, the Columbia Center for Urban Agriculture is a non-profit that educates and supports communal and personal gardens of low income residents to provide fresh, healthy food. Using these precedents as models, focus groups and interviews were conducted with clients, staff, administrators and local community members of the sites above to identify key drivers of successful social integration of vulnerable populations, including the developmentally disabled. The key drivers identified include community acceptance, stability and freedom, social interaction, employment, and outdoor activity. The goal and purpose of this research was to develop a method for increasing the health and wellbeing of individuals with developmental disabilities, mental illness, and other socially isolated populations in Mexico, Missouri. The implemented project will reduce stigmatization, increase job opportunities and access to nature, and promote acceptance in communities across America. The proposed project is intended to transform Mexico into a place of understanding and acceptance of people with developmental disabilities. Although Mexico was selected as the project site, this project is intended to be a demonstration for other rural communities in the United States and illustrate that bridging deep social gaps is possible if approached in a sustainable, systemic way. As such, this project will serve as model to inspire other communities to follow—creating meaningful impact that ripples throughout the U.S. Inspired by community projects that have successfully destigmatized developmentally disabled individuals and other vulnerable populations, this study asked what steps can Mexico take to integrate developmentally disabled residents into the community, while also increasing opportunities to experience nature and providing employment? Sub-questions included: How does care for the developmentally disabled community currently function in Mexico, MO? What job opportunities exist in Mexico, MO for the developmentally disabled? What best practices from Geel, Broadway Housing Communities, Gould Farm, Columbia Center for Urban Agriculture, and LifeWorks can be applied to Mexico, MO? How could a community garden project be applied in Mexico, MO to encourage personal connections? At the project site in Mexico, focus groups, interviews and a public community survey were conducted to identify the needs of the community’s developmentally disabled population living in supportive environments and how participating residents could interact with this population. The needs identified include increasing access to social interactions with other community members, increasing connections and access to fresh foods, getting outdoors regularly, going on an ‘outing’ or other activity that involves leaving regularly as something to anticipate, creating opportunities for continual learning, and consistency of presence in the community. To satisfy all these criteria, this study proposes a neighborhood gardening collective called “Friendly Front Gardens” to foster community integration of developmentally disabled residents living in independent supported living homes. By increasing access to casual interactions with other community members, this normalizes engaging with the developmentally disabled and other traditionally isolated populations in the public realm. If caretakers, their clients, and community members learned about food together, they would have something to bond over and enrich the rest of their lives. Helping the community by growing gardens together fosters a neighborliness and shared pride that creates community cohesion.
Keywords: Rural; Developmental disabilities; Mental health; Landscape architecture